Suicide behavior is associated with childhood emotion dysregulation but not trait impulsivity in first episode psychosis - Grattan, Rebecca E. (Psychiatry Res, 2020)
Historically, research on suicide behavior has not included those experiencing first episode psychosis (FEP), hindering prevention efforts for this population. Emotion dysregulation and impulsivity represent two mechanisms that contribute to suicide, but these have not been examined in FEP. We hypothesize that the combination of trait impulsivity and childhood emotion dysregulation are associated with suicide behavior (SB) and ideation (SI) in those experiencing FEP. Participants were recruited from an Early Psychosis Program (N=80, ages 12-32, 65% male). Clinician ratings of symptoms and history of SI and SB were obtained at baseline. Participants also completed self-report measures of childhood emotion dysregulation and trait impulsivity. Regression analyses examined whether childhood emotion dysregulation and trait impulsivity individually or in combination were associated with SI and SB, and the severity of SI and SB. Childhood emotion dysregulation was significantly associated with a history of SB and its severity, but not SI. Attention impulsivity was associated with the severity of SI. However, other impulsivity types, and interactions were not associated with a history of SI or SB. This suggests childhood emotion dysregulation is a potential target for prevention of SB in FEP, while trait impulsivity may be less important in this effort.